IMPLEMENTATION OF ACTIVE DYNAMIC FILING MANAGEMENT IN SUPPORTING ADMINISTRATIVE SERVICES AT CV NUSA PUTRA IN JAKARTA - Maya Sofiana; Endang Supriyadi; Herlinawati, Herlinawati (Journal of Social and Economics Research, 2025)
This research aims to find out how to digitize SAP-based incoming goods process administration services (Systems Applications and products in Data Processing) at the Production Unit at Pertamina Lubricants, to find out what obstacles are faced in digitizing SAP-based incoming goods process administration services at the Production Unit at Pertamina Lubricants, and what efforts have been made to overcome obstacles in digitizing SAP-based incoming goods process administration services at the Production Unit at Pertamina Lubricants. The focus of this observation is on what stages are carried out in the SAP-based incoming goods process administration services at the Production Unit at Pertamina Lubricants. Data collection methods are based on direct observation and in-depth interviews with informants. Based on the research results, the digitization of SAP-based incoming goods processing administration services at the Production Unit at Pertamina Lubricants has been implemented in accordance with the provisions set by the company and the existing obstacles are felt to be not too significant.